2021
DOI: 10.33423/jhetp.v21i8.4514
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of the Barriers to and Benefits From Service-Learning

Abstract: With the increased use of service-learning (SL) experiences across disciplines, researchers have considered challenges and benefits for various stakeholders to the use of SL as a pedagogical strategy in the classroom. Primarily, the challenges have been framed from the faculty's perspective, and the benefits measured have been for undergraduate students. We address the gap in the literature by examining student perceptions of both barriers and benefits in a graduate program. Our results indicate that perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…They did not perceive service-learning courses to be more work or require more time than their traditional courses, which contrasts with findings from recent literature. Xavier and Jones (2021) reported that, of their 80 Master's level students, mean scores for the pre-service-learning survey indicated that students thought it moderately likely they would have less time to work on their other schoolwork, have less free time, and less time to spend with their families because of the servicelearning course. Colvin (2020) also noted that approximately half of undergraduate students enrolled in a service-learning course felt strongly about the perceived workload and time consumption of the service-learning project.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They did not perceive service-learning courses to be more work or require more time than their traditional courses, which contrasts with findings from recent literature. Xavier and Jones (2021) reported that, of their 80 Master's level students, mean scores for the pre-service-learning survey indicated that students thought it moderately likely they would have less time to work on their other schoolwork, have less free time, and less time to spend with their families because of the servicelearning course. Colvin (2020) also noted that approximately half of undergraduate students enrolled in a service-learning course felt strongly about the perceived workload and time consumption of the service-learning project.…”
Section: Discussionmentioning
confidence: 99%
“…Our research seeks to build on the limited repository of literature on student perceptions of service-learning to address this knowledge gap. While most of the existing perception-based research seeks student perceptions on the service-learning program or course itself (Currie-Mueller and Littlefield, 2018; Keles and Altinok, 2020;Xavier and Jones, 2021;Williams, 2022), it is also important to ask students about their perceived benefits of service-learning as compared to the benefits of a traditional course. By focusing on student perceptions, it is possible to portray apprehensions and outlooks regarding service-learning to better inform course and program practices (Xavier and Jones, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because students often have outside family or work obligations, this practice can help alleviate any added stress to an already packed curriculum and allow students to make any necessary arrangements ahead of time (eg, finding a babysitter, finding transportation, requesting time off work, etc). 18 The strengths of our scoping review include using multiple databases (Pubmed, CINAHL, Scopus, and Embase) to retrieve articles, having a very broad literature search criteria, having the literature search performed by a senior librarian (CHS), and having clear inclusion and exclusion criteria. However, as with any study, it also had its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Because students often have outside family or work obligations, this practice can help alleviate any added stress to an already packed curriculum and allow students to make any necessary arrangements ahead of time (eg, finding a babysitter, finding transportation, requesting time off work, etc). 18…”
Section: Discussionmentioning
confidence: 99%